2019
DOI: 10.1371/journal.pone.0207733
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and resistance for antimycobacterial activity of a fluoroquinophenoxazine compound

Abstract: We have previously reported the inhibition of bacterial topoisomerase I activity by a fluoroquinophenoxazine compound (FP-11g) with a 6-bipiperidinyl lipophilic side chain that exhibited promising antituberculosis activity (MIC = 2.5 μM against Mycobacterium tuberculosis , SI = 9.8). Here, we found that the compound is bactericidal towards Mycobacterium smegmatis , resulting in greater than 5 Log 10 reduction in colony-forming units [cfu]/mL … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, ethacridine and echinomycin are two DNA intercalators and bind to DNA with high affinity. 45,54 They also potently inhibited E. coli DNA gyrase activities (Figure S3c,d), although DNA intercalation/unwinding of pAB1_FL905 by these two intercalators interferes with the fluorescence signal detection (Figure S3a,b). In fact, many DNA intercalators are among the hits of this HTS campaign (Table S3).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ethacridine and echinomycin are two DNA intercalators and bind to DNA with high affinity. 45,54 They also potently inhibited E. coli DNA gyrase activities (Figure S3c,d), although DNA intercalation/unwinding of pAB1_FL905 by these two intercalators interferes with the fluorescence signal detection (Figure S3a,b). In fact, many DNA intercalators are among the hits of this HTS campaign (Table S3).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Second, unlike previous HTS efforts mainly targeted the gyrB ATPase domain of bacterial gyrase, this HTS assay, employed relaxed DNA as the substrate, would identify inhibitors that affect all possible steps of the catalytic cycle of E. coli DNA gyrase, including DNA binding, DNA cleavage, strand passage, and DNA relegation. For example, ethacridine and echinomycin are two DNA intercalators and bind to DNA with high affinity. , They also potently inhibited E. coli DNA gyrase activities (Figure S3c,d), although DNA intercalation/unwinding of pAB1_FL905 by these two intercalators interferes with the fluorescence signal detection (Figure S3a,b). In fact, many DNA intercalators are among the hits of this HTS campaign (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Derivative 11a with 6-methylpiperazinyl and 9-amino groups ( Figure 6 , IC 50 = 0.48 µM) showed broad spectrum antibacterial activity (MICs = 0.78–7.6 µM) against bacteria that include Gram-negative E. coli and M. tuberculosis . Derivative 11g with the 6-bipiperidinyl lipophilic substitution showed the most promising antitubercular activity (MIC = 2.5 µM, selectivity index (SI) = 9.8) and was also active (MIC = 50 µM) against a clinical isolate of Mycobacterium abscessus [ 114 , 115 ]. The mechanism of resistance in mycobacteria was investigated by stepwise isolation of resistant mutants in M. smegmatis followed by comparison of the whole-genome sequence of the original strain and mutant isolates.…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
“…The mechanism of resistance in mycobacteria was investigated by stepwise isolation of resistant mutants in M. smegmatis followed by comparison of the whole-genome sequence of the original strain and mutant isolates. Mutations in genes that affect compound entry and retention were identified instead of mutations in the topoisomerase I gene that might confirm the enzyme as the antibacterial target [ 115 ]. Biophysical analysis showed that DNA binding by fluoroquinophenoxazine 11g may contribute to the antibacterial mechanism, but could not account entirely for the direct binding and potent inhibition of the mycobacterial topoisomerase I [ 115 ].…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%